Politicians, Social Media, and Digital Publics: Old Rights, New Terrain. (October 2020) - Sobieraj, Sarah; Masullo, Gina M.; Cohen, Philip N.; Gillespie, Tarleton; Jackson, Sarah J.
In this interdisciplinary roundtable discussion, five scholars interested in political communication work through the democratic dilemmas created when privately owned social media platforms are used as digital public squares by elected officials in the United States. This conversation unfolds in the context of ongoing legal cases that challenge politicians' efforts to block select interlocutors and bar them from participation. We grapple with the tension between politicians' use of social media to broadcast their own messages as a form of publicity with the desire by some members of the public that politicians be transparent online by allowing the electorate to question or even criticize them. Through this discussion, we weigh the importance of the right to criticize the government and its leaders alongside the realities of contentious content on social media platforms that are rife with abusive content, in a cultural context marked by social inequalities.